Effects of Prenatal Exposure to Inflammation Coupled With Stress Exposure During Adolescence on Cognition and Synaptic Protein Levels in Aged CD-1 Mice - Zhang, Zhe-Zhe; Zhuang, Zhan-Qiang; Sun, Shi-Yu; Ge, He-Hua; Wu, Yong-Fang; Cao, Lei; Xia, Lan; Yang, Qi-Gang; Wang, Fang; Chen, Gui-Hai (Frontiers in Aging Neuroscience, 2020)
Age-associated impairment of spatial learning and memory ability (AISLM) presents substantial challenges to our health and society. Increasing evidence indicates that embryonic exposures to inflammation accelerate AISLM, which could be attributable to changed synaptic plasticity associated various proteins at certain extent. However, it is still uncertain whether the factors of social psychology affect this AISLM and genes expression of synaptic proteins. Synaptotagmin-1 (Syt-1) and activity-regulated cytoskeleton-associated protein (Arc) are synaptic proteins closely related to cognitive functions. In this study, CD-1 pregnant mice received intraperitoneal injection of lipopolysaccharides (50 μg/kg) or normal saline daily at days 15-17 of gestation, and the half offspring of each group were given stress during adolescence for 28 days. Morris water maze (MWM) was used to evaluate the spatial learning and memory ability at age of 3 and 15 months separately. Western blotting and RNA-scope technology were used to detect the protein and mRNA levels of Arc and Syt-1 in the hippocampus. The results showed that 15-month-old control mice showed worse cognitive ability and higher protein and mRNA levels of Arc and Syt-1 compared to their younger counterparts. Embryonic inflammatory exposure or with adolescent stress aggravated the AISLM and the age-related increase of Arc and Syt-1 expression. Moreover, the protein and mRNA levels of hippocampal Arc and Syt-1 significantly correlated with the performance in the learning and memory periods of MWM, especially in the mice with adverse insult in early life. Our findings indicated that prenatal exposure to inflammation or with adolescent stress could exacerbate the AISLM and age-related enhance of Arc and Syt-1 expressions, which is linked to the cognitive impairments in CD-1 mice with exposure to adverse factors in early life.